Is There Madness in the Method? Researching Flexibility in the Education of Adults - Julia Clarke; Richard Edwards; Roger Harrison (Adult Education Research Conference, 2000)
This paper explores the process of formulating research questions for an ongoing empirical study of conceptions of flexibility and lifelong learning in the context of further education in the UK. The process is represented in three parallel versions: an algorithmic tale, a tale of improvisations and a reflexive tale.